A new sesquiterpene from Lebanese wild carrot inhibits proliferation of human acute myeloid leukemia cells - Boulos, J. (2016)
Daucus carota L. ssp. carota (Apiaceae), also known as wild carrot, is a commonly used medicinal plant in folk medicine worldwide for the treatment of several ailments including cancer [1]. Earlier studies in our labs revealed that the acetone: methanol oil extract of the plant possesses potent anticancer activity against a panel of acute myeloid leukemia (AML) cells [2]. The aim of the present study was to isolate the active compound(s) and evaluate its anticancer activity. Successive column chromatography and fractionation led to the isolation of a new sesquiterpene unique to the Lebanese wild carrot, identified as 1β-2-himachalen-6-ol using GC-MS and 1D and 2D NMR spectroscopy. The anticancer activity of 1β-2-himachalen-6-ol was evaluated against two AML cell line, HL60 and ML2. Results revealed that the IC50 of the two latter cells were 21 and 15 µg/mL, corresponding to 94.5 and 67.5µM, respectively. Cell cycle analysis using flow cytometry revealed an increase in the sub-G1 population. Analysis of cell death after treatment with different molecule concentrations showed that cells were positive for Annexin V, PI, and active caspase staining, indicating a caspase dependent apoptotic cell death. In conclusion, 1β-2-himachalen-6-ol possesses potent anticancer activity against the tested AML cells, an effect mediated via caspase dependent apoptotic cell death.